MEMBANGUN SENTRA KELENGKENG NEW CRYSTAL BERBASIS TEKNOLOGI INFORMASI : STUDI KEDUNGWERU AYAH - Yulianto, Yulianto; Sarjimin, Sarjimin; Wibisonya, Irawan (Jurnal Abdi Insani, 2024)
Poverty is one of the problems faced by almost all regions in Indonesia. The concept of poverty relates to the estimated amount of income and the estimated amount of needs, especially needs related to basic needs or minimum basic needs so that a person can be said to live a decent life. This is often referred to as the concept of absolute poverty. Poverty is a person's inability to meet food needs. Based on data from the Central Java Province Village Information System, the population of Kedungweru village which falls into decile 1 to decile 4 is a number of 108 households classified as poor. The method of implementing this activity consists of providing socialization, discussion, training to the evaluation stage. It is hoped that several approaches at each stage will be able to increase the information and capabilities of partner farmer groups. The results of this activity include that partner farmer groups ultimately have knowledge related to management in managing longan farming, such as farming management, risk management and marketing management. Apart from that, future longan cultivation farming activities will have data recording related to the need for plant inputs and other supporting systems based on a system that is relatively easier and more efficient to manage in the future. In the end, this activity was able to make the partner group better at managing the longan cultivation business technically and also improve the economy of individual farmers and villages by increasing the longan seeds provided.